High-resolution melting curve analysis for genotyping of common SNP in MTHFR gene using fixed-cell suspension - Thivaratana Sinthuwiwat (2018)
Genetic variation in MTHFR might explain the interindividual differences in both therapeutic and toxic responses to the treatment of cancer and rheumatoid arthritis with methotrexate, and can be involved in the sensitivity of developing diseases like cancer and congenital anomalies. We investigated the common sequence variation, C677T, in the MTHFR gene in fixed-cell specimens archived after chromosomal analysis using a novel gene scanning method based on post PCR analysis of high-resolution melting curves (HRM). These fixed specimens were stored after routine chromosomal analysis for 1 year at -20 °C in a 3:1 methanol:acetic acid solution. The method revealed a distinct pattern between homozygous and heterozygous alleles. Sensitivity and specificity of the HRM based method were comparable to that obtained by a hybridization probe. While the success rate for genotyping of a common SNP in MTHFR was similar to the hybridization probe approach, the HRM based method was more cost-effective and had a shorter turnaround time. © 2008 Elsevier Ltd.